Use of Olive Mill Wastewater as a Growth Medium for Superoxide Dismutase and Catalase Production. Issue 5 (22nd March 2018) - Değirmenbaşı, Didem; Takaç, Serpil
Abstract : Microbial processing of food industrial waste, olive mill wastewater (OMW), is a promising route from not only a bioremediation point of view but also for bio‐refinery concept. Enzymes are among numerous products to be valorised from OMW. In this study, production of microbial antioxidant enzymes in OMW is successfully demonstrated for the first time. Superoxide dismutase (SOD) and catalase (CAT) activities by Rhodotorula glutinis cultivated in OMW in parallel with the biodegradation of wastewater are investigated. The effects of different carbon and nitrogen supplements as well as metal ions added to cultivation medium, temperature, and stress agents are examined to increase SOD and CAT activities. The results show that R. glutinis can grow and produce SOD and CAT in OMW medium. Ethanol as a carbon supplement and urea as a nitrogen supplement provide high enzyme activities. Low temperature stimulates SOD and CAT activities. Mg 2+ is the most effective metal ion for both enzyme activities. Treatment of cells with H2 O2 increases SOD and CAT activities whereas UV light did not affect the activities considerably. At all conditions, more than 75% decrease in total phenol concentration and about 75% consumption of reducing sugar presented in cultivation medium are obtained. Abstract : Microbial processing of olive mill wastewater (OMW) is a promising route for value‐added products. The production of antioxidant enzymes in the presence of OMW is demonstrated for the first time. Production and stimulation parameters for high superoxide dismutase and catalase activities by R. glutinis, such as carbon and nitrogen supplements, metal ions, temperature and stress agents, are reported.